Non-accidental injuries in children: An update for orthopaedic surgeons - Rajkumar Thangaraj; Ioannis Gigis; Konstantinos Ditsios; Mounir Hakimi; Anastasios Chytas (Journal of Orthopaedic Reports, 2022)
Background: Non-Accidental Injury (NAI) in children has significant burden on the society and is a social stigma. It is imperative that the orthopaedic surgeons are aware of the recent developments in diagnosing and managing NAI. Aim: The purpose of the study is to perform a literature review and provide an update on the NAI injuries to the orthopaedic surgeons. Seventy eight papers were selected for the review. Conclusion: Our study has shown the wide variation across the globe in definition, epidemiology, diagnostic measures, protocol and policy measures. It also highlights the difficulty in diagnosis and management of these injuries under a stressful environment and the need for multidisciplinary approach.